Забезпечення охоронної функції права : теоретико-методологічні аспекти дослідження - Дроботов, С. А.; Drobotov, S. (My University, 2010)
The article investigates the speciﬁ city of maintenance of the law protective function. The special attention is given to the analysis of the theoretical and methodological approaches in scientiﬁ c interpretation of the law protective function concept, characteristic of mechanisms and guarantees of its realization. The author determines the basic problems of realization the law protective function, shows its role for the general system of legal functions of the law.
Дроботов С. А. Забезпечення охоронної функції права : теоретико-методологічні аспекти дослідження / С. А. Дроботов // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 130-142.
Keywords: охоронна функція права; соціально-юридичні функції права; охранительная функция права; социально-юридические функции прва; watchdog function of the right; social and legal functions Prva